Granger Causality between Stock Market and Macroeconomic Indicators: Evidence from Germany - Tomáš Plíhal (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The aim of this paper is to investigate informational efficiency of the stock market in Germany. Granger causality between the stock market and the selected macroeconomic variables is investigated by bivariate analysis using Toda-Yamamoto (1995) approach. This study focuses on monthly data from January 1999 to September 2015, and the stock market is represented by blue chip stock market index DAX. Investigated macroeconomic indicators include industrial production, inflation, money supply, interest rate, trade balance and exchange rate. Stock market Granger-causes industrial production and interest rate, and is therefore leading indicator of these variables. Between money supply and stock prices is Granger causality in both directions. Other variables seem to be independent on development of the stock market. We do not find any violation of Efficient market hypothesis which indicates that the stock market in Germany is informational efficient.